Determination of the Heavy Metals in the Contaminated Soil Zones at College of Education Ibn Al-Haitham -University of Baghdad - kassir, A. F.; Yaseen, H. M.; Abu, S. B.; Aziz, M. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Soil is a crucial component of environment. Total soil analysis may give information about possible enrichment of the soil with heavy metals. Heavy metals, potentially contaminate soils, may have been dumped on the ground. The concentrations of soil heavy metals (Cd, As, Pb, Cr, Ni, Zn and Cu) were measured in three zones thought to be deeply contaminated at different depths (5, 25, 50 cm) at Ibn Al-Haitham College. The highest concentration of heavy metals Pb (63.3ppm), Cr (90.7ppm), Ni (124ppm) and Cu (75.7ppm) were found in zone (A) location-1, where the highest concentration of Zn (111.7ppm) was found in zone (C). Cd and As were detected in small amounts in all zones.     PH value, organic matters, carbonates, sulphates, chlorides and total soluble salts were also studied to get better understanding of mobility and displacement of the contaminating compounds in soil under study.